Ordering, revenue and anchoring in art auctions. (March 2015) - Hong, Harrison; Kremer, Ilan; Kubik, Jeffrey D.; Mei, Jianping; Moses, Michael
<x xml:space="preserve">Abstract</x> We estimate the effect of ordering by value on revenues in sequential art auctions held by Sotheby's and Christie's. We exploit a pre determined rotation of which of these two houses holds their auction first during auction week in New York City. When the house that goes first has relatively expensive paintings compared to the other house, we find that the sale premium for the week is around 21% higher relative to the mean sale premium, and the fraction of paintings sold during the week is around 11% higher. We provide evidence that this is due to an anchoring effect.